Approximating properties of biharmonic Poisson operators in the classes L^ψ_β, 1 - Zhyhallo, T. V.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We obtain the asymptotic equalities for the least upper bounds of the approximations of functions from the classes L^ψ_β, 1 by biharmonic Poisson operators in the integral metric.